The Effect of Group Guidance Services with Role Playing Techniques to Improve Emotional Management Skills in Al-Washliyah 12 Perbaungan High School Students - Septi Aulia Lubis; Saiful Akhyar Lubis (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the Effect of Group Guidance Services with Role Playing Techniques to Improve the Ability to Manage Emotions in Al-Washliyah 12 Perbaungan High School Students. The model in this study uses a quantitative method, an experimental model of quantitative research can be interpreted as a research method based on the philosophy of positivism, used to research a certain population or sample, data collection using research instruments, data analysis is quantitative/statistical with the aim of testing the hypothesis that has been set. Based on the output of "Test Statistics" above, it can be seen that Asymp. Sig. (2-tailed) is worth 0.043. Because the value of 0.043 ˂ 0.05, it is concluded that H1 is accepted. Which is an increase in the control of angry emotions of Al-Washliyah 12 Perbaungan High School students after being given role playing group counseling. So it can be said that the influence of group guidance services with role playing techniques can improve the ability to manage emotions in Al-Washliyah 12 Perbaungan High School students.